2014
DOI: 10.18632/genesandcancer.20
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Id1 and Id3 promotes tumorigenicity by enhancing angiogenesis and suppressing apoptosis in small cell lung cancer

Abstract: Constant deregulation of Id1 and Id3 has been implicated in a wide range of carcinomas. However, underlying molecular evidence for the joint role of Id1 and Id3 in the tumorigenicity of small cell lung cancer (SCLC) is sparse. Investigating the biological significance of elevated expression in SCLC cells, we found that Id1 and Id3 co-suppression resulted in significant reduction of proliferation rate, invasiveness and anchorage-independent growth. Suppressing both Id1 and Id3 expression also greatly reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…High ID1/ID3 expression in ILC tumors was associated with downregulation of cell cycle-related genes, which is in contrast to the proliferative effects of ID1 and ID3 in anchorage-independent conditions, and with upregulation of pathways associated with angiogenesis and the matrisome. While these results are based on correlation analyses, they are largely consistent with previous reports in other contexts 27 , 31 , 44 , 56 and should be validated in further functional studies. Taken together, these data suggest that ID1 and ID3 may play roles in multiple stages of tumor growth and metastasis by regulating different processes in attached versus detached cancer cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…High ID1/ID3 expression in ILC tumors was associated with downregulation of cell cycle-related genes, which is in contrast to the proliferative effects of ID1 and ID3 in anchorage-independent conditions, and with upregulation of pathways associated with angiogenesis and the matrisome. While these results are based on correlation analyses, they are largely consistent with previous reports in other contexts 27 , 31 , 44 , 56 and should be validated in further functional studies. Taken together, these data suggest that ID1 and ID3 may play roles in multiple stages of tumor growth and metastasis by regulating different processes in attached versus detached cancer cells.…”
Section: Discussionsupporting
confidence: 90%
“…ID1 and ID3 have previously been characterized as part of a common murine and human lung metastatic signature in triple negative breast cancer cells 28 , 29 and extensively validated as regulators of metastasis 27 , 28 , 30 . ID1 and ID3 have also been implicated in anchorage-independent growth in soft agar in small cell lung cancer 31 ; however, they have not previously been studied in ILC. Through a series of functional in vitro experiments using cell lines and in silico analyses of patient tumors, herein we have discovered a role for ID1 and ID3 as novel drivers and potential therapeutic targets for ILC.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, genes in clusters 3 and 4 were associated with an unfavorable prognosis in glioma. For example, Annexin A2 ( ANXA2 ), Ferritin Light Chain ( FTL ), and Inhibitor of DNA-binding-1 ( ID1 ) fulfill important tumor functions in glioma and glioblastoma, such as the promotion of invasion and tumor progression 42 , proliferation 26 , or chemoresistance 43 45 . The fourth cluster included detrimental genes such as ALDH1A3 promoting stemness-like features in glioma, and is associated with worse survival 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer HCT116 cells, ID1 inhibited apoptosis induced by chemotherapy drugs and ultraviolet light [27] . In small cell lung cancer, it has been reported that the high expression of ID1 can signi cantly inhibit the apoptosis of tumor cells [28] . Our study is highly in line with results of these former studies.…”
Section: Discussionmentioning
confidence: 99%